A Rare Association of Congenital Diaphragmatic Hernia with Lower Esophageal Atresia and Perforation - Narendra Kumar Are; K. Nagarjuna; Lavanya Kannaiyan (Hindawi Limited, 2010)
Congenital diaphragmatic hernia is known to be associated with esophageal atresia, which is a rare association. We report a rare occurrence of congenital diaphragmatic hernia and lower esophageal atresia.